The 12th Conference of the International Sports Engineering Association 2018
DOI: 10.3390/proceedings2060259
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Competition Wheelchair Based on Estimation of Muscle Activity for Forward Linear Operation by Using Inverse Dynamics Analysis

Abstract: The objective of this study was to evaluate an optimum structure for a rugby wheelchair by estimating the muscle force during forward linear operation of the wheelchair using an inverse dynamics analysis. The simulation model was represented by restraining the contact area between the frame and seat of the wheelchair and the body model. Three body model variations were constructed with different degrees of disability. Wheelchair models were also constructed by varying the range of camber angle, wheel diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As shown in Table 1, the muscle strength of each part is set as a percentage of healthy subjects according to the class of the disability. The reason is that our previous study identified the trend that the triceps muscle plays a role in maintaining posture in addition to propulsion when the trunk muscle strength is lower [4].…”
Section: Construction Of Body Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Table 1, the muscle strength of each part is set as a percentage of healthy subjects according to the class of the disability. The reason is that our previous study identified the trend that the triceps muscle plays a role in maintaining posture in addition to propulsion when the trunk muscle strength is lower [4].…”
Section: Construction Of Body Modelmentioning
confidence: 98%
“…Therefore, if it would be possible to evaluate competition wheelchairs by taking into account the physical load of the athlete, finding a suitable wheelchair for the athlete individually may lead to the reduction of injury risk and improvement of the performance. In our previous study [4], although the muscle activity during the forward linear operation was estimated using the musculoskeletal simulation, the wheelchair operation was expressed not by the real measured motion but by the virtual motion. In addition, the relationship between the physical load and the operability could not be discussed in detail due to a lack of sufficient accuracy validation of the simulation results as well as the virtual motion.…”
Section: Introductionmentioning
confidence: 99%